The British general election (2010) and the political consciousness of the market-state - Lewkowicz, Nicolas (Rivista di studi politici internazionali, 2010)
<!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The demise of the Cold War brought with it a significant transformation of the international order. This transformation entailed the end of the political and economic symbiosis between the Western democracies and communism. The riddance of this symbiosis gave rise to a gradual entrenchment of ‘conservative democracy’, understood as the unwitting rejection of the remnants of the social democratic consensus by large segments of the population which, paradoxically, still benefit from it. This process consolidates ‘conservative democracy’ as the political consciousness of the market-state. La fin de la guerre froide a entraîné une transformation significative de l’ordre international. Cette transformation a impliqué la fin de la symbiose politique et économique des démocraties occidentales et du communisme. L’arrêt de cette symbiose a déterminé l’affermissement graduel d’une ‘démocratie conservatrice’ en tant que refus inconscient des restes du consensus social démocratique par des larges segments de la population qui, paradoxalement, continuent à en bénéficier. Ce processus affermit une ‘démocratie conservatrice’ en tant que conscience politique de l’État-marché. KEY WORDS: Conservative democracy; ‘Symbiosis-paradox’; Market-state; Cold War; British democracy.